Obtenção e caracterização de óxido de cério, obtido a partir da decomposição térmica do tris(8-hidroxiquinolinato)cério(III) - Cavasotto, Thiago (2015)
In the present work, it was investigated the influence of the final pH of precipitation, agitation time and mode of agitation, which assessed the mechanical agitation mode and ultrasound to obtain the cerium dioxide. For process optimization, it was used a tool called Planning Factor, which provides an estimative of better conditions, considering a response variable from the experimental data. The responsible variable adopted in this work was Decomposition Final Temperature and Particle Average Size. The cerium dioxide was obtained from the thermal decomposition of the complex tris (8-hydroxyquinolinate) cerium (III), synthesized by chemical precipitation using 8-hydroxyquinolinechelator and characterized by infrared spectroscopy (FTIR) and scanning electronic microscopy (SEM). In addition, it was performed the study of the complex thermal behavior with assistance of thermogravimetry (TG), derivative thermogravimetry (DTG) and differential thermal analysis (DTA); The cerium dioxide was characterized by FTIR and X-ray diffraction (XRD), in which it was based to the determination of the particle average size using Scherrer's formula. The Factorial design pointed out to response variable Decomposition Final temperature that, for both modes of agitation, the best synthesis conditions are for higher values of final pH's precipitation. Also, the stirring time had no significant influence when used the 95% significance studied range. For response variable Average Size, the test pointed out to both ways of stirring, when none of the variables had significant influence at 95% significance within the studied range, assigning the average particle size only to the method of synthesis. Thereby, there was no significant difference between the stirring modes.